Central Metabolism Is Tuned to the Availability of Oxygen in Developing Melon Fruit - Mori, Kentaro; Beauvoit, Bertrand P.; Biais, Benoît; Chabane, Maxime; Allwood, J. William; Deborde, Catherine; Maucourt, Mickaël; Goodacre, Royston; Cabasson, Cécile; Moing, Annick; Rolin, Dominique; Gibon, Yves (Frontiers in Plant Science, 2019)
Respiration of bulky plant organs such as fleshy fruits depends on oxygen (O2) availability and often decreases with O2 concentration to avoid anoxia, but the relationship between O2 diffusional resistance and metabolic adjustments remains unclear. Melon fruit (Cucumis melo L.) was used to study relationships between O2 availability and metabolism in fleshy fruits. Enzyme activities, primary metabolites and O2 partial pressure were quantified from the periphery to the inner fruit mesocarp, at three stages of development. Hypoxia was gradually established during fruit development, but there was no strong oxygen gradient between the outer- and the inner mesocarp. These trends were confirmed by a mathematical modelling approach combining O2 diffusion equations and O2 demand estimates of the mesocarp tissue. A multivariate analysis of metabolites, enzyme activities, O2 demand and concentration reveals that metabolite gradients and enzyme capacities observed in melon fruits reflect continuous metabolic adjustments thus ensuring a timely maturation of the mesocarp. The present results suggest that the metabolic adjustments, especially the tuning of the capacity of cytochrome c oxidase to O2-availability that occurs during growth development, contribute to optimising the O2-demand and avoiding the establishment of an O2 gradient within the flesh.